DAMPAK PEMBERIAN REWARD TERHADAP MOTIVASI BELAJAR SISWA DI KELAS VIII SMP NEGERI 4 ULUNOYO - Roswita, Roswita Halawa (Universitas Nias Raya, 2024)
The background to this research problem is the impact of giving rewards on student learning motivation. The research objectives are 1) To determine and describe the impact of giving rewards on student learning motivation. 2) To find out and describe how students are motivated to learn. This research uses qualitative research. The research subjects were class VIII students. Research results 1) The impact of giving rewards on students' learning motivation in learning, students are more active in learning, triggering student involvement in the learning process 2) Students' learning motivation before giving rewards, many students are lazy in doing assignments, very rarely ask or answer questions from the teacher, and student learning motivation after giving rewards to students shows a more active learning attitude in learning, doing assignments on time, quickly completing and submitting assignments, calm and orderly in the learning process. The conclusion of the research is that the impact of giving rewards on student learning motivation is very positive, students are more active in learning, triggering student involvement in the learning process. Researchers provide several suggestions, namely 1) The impact of rewards should be more positive in increasing students' learning motivation through providing educational rewards. 2) Students' learning motivation should be further increased by teachers in PPPKn and subject areas through providing rewards and applying various learning methods.